Pelatihan Self-Reguated Learning pada Mahasiswa PGSD Universitas Mataram Di Era New Normal - Iva Nurmawanti; Darmiany, Darmiany; Istiningsih, Siti; Nurwahidah, Nurwahidah (Universitas Nusantara PGRI Kediri, 2022)
The purpose of this training is to motivate students regarding self-regulation in learning. Especially for 7th-semester students of Mataram University PGSD study program who have a high learning load, especially in completing the thesis. Higher learning challenges are also supported due to the pandemic era situation where all activities are limited. The method used is in three stages, namely designing training activities and materials, carrying out activities, and training results. This training is carried out online through a zoom meeting. The activities were carried out smoothly and the participants were very enthusiastic about participating in the training from beginning to end. Some participants were also enthusiastic about asking questions related to the obstacles they faced in learning. The posttest results also showed that 79% of students were able to answer all the post-test questions correctly. This shows that this training can have a good impact on students, especially regarding independent learning.